Analysis of the Application of Criminal Sanctions against Companies Paying Labor Wages Below the Regency / City Minimum Wage - Dirhamfathurusi Dirhamfathurusi (IHSA Institute, 2019)
Wages are the rights of workers or employees received and expressed in the form of money as compensation from employers or employers to workers who are determined and paid according to a work agreement, agreement or legislation, criminal sanctions against companies (entrepreneurs) who make wages workers below the minimum wage can be seen from the number of violations of workers 'rights, especially the practice of paying workers' wages below the provincial minimum wage standard, the existence of criminal sanctions did not reduce the criminal acts not repeated, for example in Lampung province. The problem in this thesis is how to enforce criminal sanctions against companies that pay labor wages below the Regency / City minimum wage and what factors hinder enforcement of criminal sanctions against companies that pay labor wages below the Regency / City minimum wage. The approach of the problem in this paper is a normative juridical and empirical juridical approach. The sources and types of data used are primary data and secondary data. Determination of sources is done by interviewing respondents. The method of data collection is done by literature study and field studies. Based on the results of the research and discussion on the results of the study, it was concluded that the company violated the Regency / City Minimum Wage provisions, so the worker could take a criminal effort, namely reporting to the labor inspectors at the Manpower Office. The inhibiting factor is the existence of lameness from the substance of Law No. 13 of 2003 concerning Manpower. The number of labor inspectors in Lampung Province is not comparable to the number of companies supervised. The community, especially workers / laborers, do not know about the existence of criminal facilities. Lack of public awareness of the importance of law enforcement in the field of employment. The suggestion in this study is that labor inspectors should increase socialization to companies regarding minimum wage provisions. Workers /laborers are expected to be able to report to labor inspectors if the rights as workers get wages below the minimum.